Enhancing visual analysis of environmental monitoring data through an information visualization-based prototype - Silva, Celmar Guimarães da; Umbuzeiro, Gisela de Aragão (Anais do Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais (WCAMA); 2010: Anais do II Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais, 2010)
This paper presents an approach for using interactive visual data representation in the field of environmental monitoring. Monitoring programs of dredged material disposition areas generates lots of spreadsheets, each one containing thousands of data necessary for decision making. This paper proposes using Information Visualization techniques for enhancing visual data analysis, aiming to ease the detection of important patterns and trends in these datasets. An implemented prototype organizes this data in a way that it could be easily available for users' interactive and visual-based queries.